Triple-mode grid-balancing plants via biomass gasification and reversible solid-oxide cell stack: Concept and thermodynamic performance. (15th December 2020) - Wang, Ligang; Zhang, Yumeng; Li, Chengzhou; Pérez-Fortes, Mar; Lin, Tzu-En; Maréchal, François; Van herle, Jan; Yang, Yongping
Abstract: Biomass-to-electricity or -chemical via power-to-x can be potential flexibility means for future electrical grid with high penetration of variable renewable power. However, biomass-to-electricity will not be dispatched frequently and becomes less economically-beneficial due to low annual operating hours. This issue can be addressed by integrating biomass-to-electricity and -chemical via "reversible" solid-oxide cell stacks to form a triple-mode grid-balancing plant, which could flexibly switch among power generation, power storage and power neutral (with chemical production) modes. This paper investigates the optimal designs of such a plant concept with a multi-time heat and mass integration platform considering different technology combinations and multiple objective functions to obtain a variety of design alternatives. The results show that increasing plant efficiencies will increase the total cell area needed for a given biomass feed. The efficiency difference among different technology combinations with the same gasifier type is less than 5% points. The efficiency reaches up to 50%–60% for power generation mode, 72%–76% for power storage mode and 47%–55% for power neutral mode. When penalizing the syngas not converted in the stacks, the optimal plant designs interact with the electrical and gas grids in a limited range. Steam turbine network can recover 0.21–0.24 kW electricity per kW dry biomass energy (lower heating value), corresponding to an efficiency enhancement of up to 20% points. The difference in the amounts of heat transferred in different modes challenges the design of a common heat exchange network. Highlights: Novel concept of triple-mode grid balancing plant for high annual operating hours. Power-generation, -storage and -neutral modes enabled to produce power or methane. A decomposition-based optimization method to identify potential business cases. A pool of optimal conceptual plant designs obtained for optimal grid integration. High efficiencies of all modes achieved with the aid of steam turbine network.